2010
DOI: 10.1143/jjap.49.09mc05
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures Related to Ferroelectric Properties in (Bi0.5K0.5)TiO3–BiFeO3

Abstract: Crystal structures and microstructures associated with ferroelectric properties in a lead-free piezoelectric compound, x(Bi0.5K0.5)TiO3–(1-x)BiFeO3, have been investigated mainly by transmission electron microscopy (TEM). Complicated ferroelectric domain structures with a width of approximately ∼200 nm were found in the polar rhombohedral structure of the x = 0.30 compound. On the other hand, a tweed-like contrast, which stems from local lattice distortion, was observed in the pseudocubic structure of the x = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…19 The extrinsic contribution to the piezoelectric effect is small and is proposed to be due to low ferroelastic domain wall mobility. 20 The xBiFeO 3 -(1 À x)(K 0.5 Bi 0.5 )TiO 3 (BF-KBT) system has recently been reported, [21][22][23][24][25] as with many lead-free materials a number of difficulties were experienced during fabrication and densification using conventional sintering techniques. The BiFeO 3 rich compositions, where x < 0.7 belong to the rhombohedral R3c phase as determined using laboratory X-rays and neutron diffraction.…”
mentioning
confidence: 99%
“…19 The extrinsic contribution to the piezoelectric effect is small and is proposed to be due to low ferroelastic domain wall mobility. 20 The xBiFeO 3 -(1 À x)(K 0.5 Bi 0.5 )TiO 3 (BF-KBT) system has recently been reported, [21][22][23][24][25] as with many lead-free materials a number of difficulties were experienced during fabrication and densification using conventional sintering techniques. The BiFeO 3 rich compositions, where x < 0.7 belong to the rhombohedral R3c phase as determined using laboratory X-rays and neutron diffraction.…”
mentioning
confidence: 99%
“…23 However, the dielectric and piezoelectric properties characterized as a function of composition showed rather ambiguous 3 behavior with respect to the MPB. Ref.…”
mentioning
confidence: 99%
“…As reported in Refs. 21,23 , a structural phase boundary at x ≈ 0.6 takes place in the system. It can be recognized by the vanishing diffraction line (113)R3c and the splitting of the (111)C reflection.…”
mentioning
confidence: 99%
“…At x = 0.4, no obvious peak splitting is observed in the {111} or {200} family of planes indicative of a transition to a pseuocubic phase, in contrast to other studies who noted this transition at x = 0.6 [13][14]. It has been suggested that the pseudocubic phase is characterized by nanodomain structures consisting of non-polar cubic and polar rhombohedral structures of the order of 10 nm identified using TEM [11], therefore explaining the absence of rhombohedral or tetragonal splitting using conventional laboratory X-rays. Minor tetragonal peak splitting was observed in the {200} reflection for x = 0.1, characteristic of the transition to the tetragonal phase although these samples were undersintered (although any increase in sintering temperature resulted in melting of the samples), and may explain the difficulty in observing this transition clearly.…”
Section: Methodsmentioning
confidence: 68%
“…Recently, the xBiFeO 3 -(1-x)(K 0.5 Bi 0.5 )TiO 3 system has been fabricated [10][11][12][13], notably exhibiting a "pseudocubic" region where long-range crystallographic order is frustrated coupled with large electric-field induced strains dominated by the electrostrictive component. A series of publications [13][14] have elucidated the origin of the relaxor-like dielectric properties at high temperature across the compositional space, owed to MaxwellWagner relaxation rather than conventional relaxor behavior [16].…”
Section: Introductionmentioning
confidence: 99%